Hemofagocytární syndrom (Kazuistika a review literatury) - Oborilová, A; Mayer, J; Pavlík, P; Buliková, A; Vorlícek, J (Vnitrni lekarstvi, 2003)
The haemophagocytic syndrome (HPS) is clinically characterized by fever, pancytopenia and hepatosplenomegaly. Usually it takes an acute course with a high mortality. The pathogenetic basis is inadequate activation of the immune system--in particular Th1-lymphocytes with subsequent overproduction of cytokines and extreme activation of macrophages with haemophagocytosis. The activated cells infiltrate organs, cause tissue damage and clinical manifestations of the syndrome. From the etiological aspect two forms exist: primary (familial) with autosomal recessive inheritance and the secondary form which forms a heterogeneous sub-group, caused as a rule by infection and/or a tumour. The prognosis seems somewhat more favourable in secondary forms. In treatment which is essentially the same for both forms, chemotherapy combined with immunosuppression proves useful, in more aggressive forms chemotherapy as used in the treatment of non-Hodgkin lymphomas. The only curative method is transplantation of haematopoietic stem cells which is also the treatment of first choice in the familial form of haemophagocytosis. In the submitted paper the authors present a review of contemporary knowledge on this treacherous and relatively rare entity. The haemopgagocytic syndrome should be always taken into account in the differential diagnosis of fever with an obscure etiology. The authors assume that the haemophagocytic syndrome is rarely considered in practice and therefore is usually inadequately diagnosed and thus not treated in time. In the conclusion the authors describe the case-records of a 26-year-old female patient with haemophagocytic syndrome which developed during pregnancy.
Keywords: komplikace těhotenství; Female; histiocytóza z non-Langerhansových buněk; dospělí; Adult; Histiocytosis, Non-Langerhans-Cell; Pregnancy; Humans; diferenciální diagnóza; ženské pohlaví; Diagnosis, Differential; lidé; Pregnancy Complications; těhotenství